Diversity of Butterflies in Ledokombo Hillocks Jember, East Java, Indonesia - Husni Mubarok; Alfina Eka Dwi Candra; Bayu Sandika; Wiwin Maisyaroh; Ellena Yusti; Agmal Qodri (Universitas Gadjah Mada, 2023)
Ledokombo hillocks are small hills located in Jember, East Java that have natural resources and face habitat alteration such as plantation and mining. However, a study of the diversity of butterflies has not been carried out in this area. We analysed the diversity of butterflies using the Shannon-Wiener diversity index (H’) and Pielou evenness index (E). We identified 514 individuals from 34 species and demonstrated a moderate diversity of butterflies (H'= 1.907) in this area. Our study results could be used for sustainable ecological management of plantations in Ledokombo Hillocks, Jember, East Java.